2022
DOI: 10.1371/journal.pone.0278041
|View full text |Cite
|
Sign up to set email alerts
|

The Austrian Osteopathic Practitioners Estimates and RAtes (OPERA): A cross-sectional survey

Abstract: Introduction Since the previous survey of the osteopathic profession in Austria was almost a decade ago, an update was necessary. The Osteopathic Practitioners Estimates and RAtes (OPERA) project was developed as a Europe-based survey, whereby an updated profile of the profession not only provides new data for Austria, but also allows for a clear comparison with other European countries. Methods A voluntary, online-based, closed-ended survey was distributed across Austria in the period between April and Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In our survey, the typical osteopath presents as female and has previously worked as a physiotherapist, as previous studies have found [ 8 ]. This is consistent with other surveys from Europe regarding osteopathy.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In our survey, the typical osteopath presents as female and has previously worked as a physiotherapist, as previous studies have found [ 8 ]. This is consistent with other surveys from Europe regarding osteopathy.…”
Section: Discussionmentioning
confidence: 69%
“…A possible reason for the heterogeneous attempts at explanation may lie in the difference in training and previous education. A recent study showed that only 17% of osteopaths surveyed in Austria identified themselves “exclusively” as osteopaths [ 8 ]. Therefore, there is a suspicion that, as our study also showed, the basic profession and nonregulation have a major influence on self-image.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…International surveys have reported that 23% to 90% of osteopaths use CST. Specifically in Europe, between 70% and 89% of the interviewed osteopaths use CST always or often [ 4 , 6 , 7 , 8 , 9 ]; and 23% to 46% use it as a first-line treatment [ 10 , 11 ]. The relationship between the craniosacral system and the mentioned diseases has been theoretically based on implausible and unproven anatomical claims and connections [ 12 ], which means that no real relationship has been established, making the use of CST less than plausible.…”
Section: Introductionmentioning
confidence: 99%